Tata Kelola Berkelanjutan: Studi Tentang Idealitas Model Tata Kelola Daerah Sulawesi Selatan, Indonesia - Abdillah Abdillah; Zahra Ahmadi (Universitas Muhammadiyah Makassar, 2022)
To overcome the conceptual ambiguity of Good Governance, based on the reinterpretation of the discourse 'from government to governance', this study uses analysis from Lange et al. (2013) on sustainable governance that focuses on political processes, institutional structures, and policies in the government of South Sulawesi as an industrial area of Eastern Indonesia. This study uses a qualitative-exploratory research method with a case study approach, using interactive analysis techniques through data collection, data reduction, data verification, data presentation, and conclusions to obtain the best findings. The results of this study find that sustainable governance in the South Sulawesi Regional Government applies a multi-dimensional approach that considers the political (political) process, government structure and policies that adequately capture the complexity of the phenomenon of governance (local governance) in Eastern Indonesia). With a good explanation of the concept with a sustainable governance model with complex multi-actor interactions/cooperation between local political elites, industry (private) civil society, as well as on the process of institutional structural interaction through what is called governance collaboration. This study contributes to recommending a sustainable governance model for local government with local wisdom of Bugis-Makassar culture in the value of siri na pacce (shame) as a value with high responsibility as a government in the South Sulawesi Government.